2022
DOI: 10.3389/ffunb.2021.802511
|View full text |Cite
|
Sign up to set email alerts
|

The First Mitochondrial Genome of Ciborinia camelliae and Its Position in the Sclerotiniaceae Family

Abstract: Ciborinia camelliae is the causal agent of camellia flower blight (CFB). It is a hemibiotrophic pathogen, inoperculate Discomycete of the family Sclerotiniaceae. It shows host and organ specificity infecting only flowers of species belonging to the genus Camellia, causing serious damage to the ornamental component of the plant. In this work, the first mitochondrial genome of Ciborinia camellia is reported. The mitogenome was obtained by combining Illumina short read and Nanopore long read technology. To resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Over the years, many aspects of C. camelliae taxonomy and its relations with the family Sclerotiniaceae have been clarified [4,39,40]. On the other hand, the information on its ecology, the relationships with both environmental factors and the host, and the uniformity of its population are still limited [1,41].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, many aspects of C. camelliae taxonomy and its relations with the family Sclerotiniaceae have been clarified [4,39,40]. On the other hand, the information on its ecology, the relationships with both environmental factors and the host, and the uniformity of its population are still limited [1,41].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive mitochondrial genome comparisons within the fungal kingdom have shown that any gene has a mitochondrial localization in all fungal species [13], suggesting that the use of mitochondrial gene diversity cannot be applied as a universal marker for fungi. Nonetheless, the analysis of mitochondrial diversity can be successfully applied to differentiate species within orders [14] or species [15,16]. For example, a unique feature apparently common in all Fusarium species is the presence of a large open reading frame with an unknown function (LV-uORF) firstly described in mitogenomes of F. graminearum, F. verticillioides and F. solani [17] and probably acquired prior to the divergence of Fusarium species.…”
Section: Introductionmentioning
confidence: 99%